Peningkatan Pendapatan Rumah Tangga Petani melalui Pemanfaatan Pekarangan (Studi Kasus di KWT Madu Serati, Desa Mambang, Kecamatan Selemadeg Timur Tabanan) - IDA AYU TRISNAYANTI SAVITRI; I KETUT SUAMBA; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Increasing household income of farmers through the utilization of yards (Case study of Madu Serati Women Farmer Group, Mambang Village, East Selemadeg District, Tabanan). Food is a basic need and has an important role in life. The government seeks to improve food security through various programs, such as the Sustainable Food House Program that utilizes house yards. This study aims to: (1) calculate the income of female farmers from the sustainable food house program, (2) calculate the contribution of female farmers' income from the sustainable food house program to the total income of farmer households, and (3) determine the motivation of female farmers to manage his yard.This research was conducted in Mambang Village, East Selemadeg District, Tabanan Regency, Bali Province from July to August 2020. The data collected were quantitative and qualitative data with primary and secondary data sources. The collected data were analyzed using both descriptive quantitative and qualitative methods. The determination of 30 samples of members of the women farmer group was conducted using non probability technique with census method. The variables measured in this study were income, contribution of income from yard and the motivation of members of the women farmer group in farming. The result shows that the average income that resulted from yard farming is IDR 2,666,196.67 with a very low contribution to total income, namely 2.75% and the motivation of the women farmer group members in working is to meet physiological needs, security needs, social needs, and appreciation needs. It is necessary to increase the number and types of vegetable crops that have high economic value.